SAWING RECOVERY OF SEVERAL SAWMILLS IN JEPARA - Malik, Jamaludin; Hopewell, Gary P (Pusat Litbang Keteknikan Kehutanan dan Pengolahan Hasil Hutan, 2011)
In the situation of wood material shortage, it is important to furniture manufacturers to efficiently utilize the wood. Increasing efficiency for improving value added of small medium enterprises of wood furniture industries in Jepara should be carried out from the first stage in wood processing: sawing that will convert logs into sawn timber. A study has been carried out on improving sawing recovery of sawntimber by live-sawing pattern to make loseware lumber for furniture material in Jepara region. This study was done by investigating the current sawing recovery data as determined during one full days processing at each of the four bandsaw mill facilities and one chainsaw/carving facility. The results indicate that the current recovery rate of sawmilling services companies in Jepara reached 70 - 80 %. These recoveries are relatively high due to the live sawing pattern used and the fact that sawn boards were not edged or resawn into square pieces at the mill. Compared to existing rules and the Government standard for calculating the recovery rate, sawmilling service companies in Jepara have practiced efficient processing in sawing.